2014
DOI: 10.1016/j.semnephrol.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Kidneys for Transplantation

Abstract: One in ten Americans suffer from chronic kidney disease, and close to 90,000 people die each year from causes related to kidney failure. Patients with end-stage renal disease are faced with two options: hemodialysis or transplantation. Unfortunately, the reach of transplantation is limited because of the shortage of donor organs and the need for immunosuppression. Bioengineered kidney grafts theoretically present a novel solution to both problems. Herein we discuss the history of bioengineering organs, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 88 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…Human renal proximal tubule cells are immunologically active, which when adapted with non-biodegradable fibres, allows membranes to act as scaffolds for the cells and as an immunoprotective barrier which previous filtration methods lacked. Phase I/II clinical trials demonstrated that the RAD was able to filter urine at a rudimentary level, improve metabolism, reduce pro-inflammatory cytokines, and improve cardiovascular stability [40], whilst improving long-term survival [41].…”
Section: Cell-integrated and Wearable Artificial Kidney Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Human renal proximal tubule cells are immunologically active, which when adapted with non-biodegradable fibres, allows membranes to act as scaffolds for the cells and as an immunoprotective barrier which previous filtration methods lacked. Phase I/II clinical trials demonstrated that the RAD was able to filter urine at a rudimentary level, improve metabolism, reduce pro-inflammatory cytokines, and improve cardiovascular stability [40], whilst improving long-term survival [41].…”
Section: Cell-integrated and Wearable Artificial Kidney Devicesmentioning
confidence: 99%
“…To recapitulate complex kidney function, epithelial, endothelial, and mesangial cells in sufficient numbers are required [41]. However, application of cell type is dependent upon the renal disease in question, therefore making it difficult to choose between tubular cells or glomerular epithelial cells, and research failed to identify whether it would be better to introduce progenitor cells for integration into existing structures or support cells which encourage existing renal parenchyma to proliferate and repair.…”
Section: Innate Kidney Repair and The Influence Of Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several paradigm shifting discoveries related to organ transplantation 1 2 3 4 5 6 7 . Chief among them includes the innovations that pertain to organ storage ex vivo 8 9 10 11 12 .…”
mentioning
confidence: 99%